White matter changes in empirically derived incident MCI subtypes in the Mayo Clinic Study of Aging. Issue 1 (31st December 2021) - Machulda, Mary M.; Lundt, Emily S.; Mester, Carly T.; Albertson, Sabrina M.; Raghavan, Sheelakumari; Reid, Robert I.; Schwarz, Christopher G.; Graff‐Radford, Jonathan; Jack, Clifford R.; Knopman, David S.; Mielke, Michelle M.; Kremers, Walter K.; et al.
Abstract: Introduction: The aim of this study was to examine white matter hyperintensities (WMH) and fractional anisotropy (FA) in empirically derived incident mild cognitive impairment (MCI) subtypes. Methods: We evaluated 188 participants with incident MCI in the Mayo Clinic Study of Aging (MCSA) identified as having one of four cluster‐derived subtypes: subtle cognitive impairment, amnestic, dysnomic, and dysexecutive. We used linear regression models to evaluate whole brain and regional WMH volumes. We examined fractional anisotropy (FA) on a subset of 63 participants with diffusion tensor imaging. Results: Amnestic and dysexecutive subtypes had higher WMH volumes in differing patterns than cognitively unimpaired; the dysexecutive subtype had higher WMH than subtle cognitive impairment. There was widespread WM degeneration in long association and commissural fibers in the amnestic, dysnomic, and dysexecutive subtypes, and corpus callosum FA accounted for significant variability in global cognition. Discussion: White matter changes likely contribute to cognitive symptoms in incident MCI.